2021
DOI: 10.3389/fbioe.2021.755964
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Mesenchymal Stem Cell Therapy With Gelatin-Based Microribbon Hydrogels in a Murine Long Bone Critical-Size Defect Model

Abstract: Mesenchymal stem cell (MSC)-based therapy and novel biomaterials are promising strategies for healing of long bone critical size defects. Interleukin-4 (IL-4) over-expressing MSCs within a gelatin microribbon (µRB) scaffold was previously shown to enhance the bridging of bone within a critical size femoral bone defect in male Balb/c mice. Whether sex differences affect the healing of this bone defect in conjunction with different treatments is unknown. In this study, we generated 2-mm critical-sized femoral di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The Wnt/β-catenin signaling pathway was significantly activated in male mice, resulting in faster fracture healing ( Haffner-Luntzer et al, 2021 ). Also, sex differences using a murine long bone critical-size defect model were compared; MSC-based therapy enhanced bone bridging with increased ALP expression especially in male mice ( Ueno et al, 2021 ). Zarei et al demonstrated sexual dimorphism with genetic and pharmacological modulation of the alternative NF-κB pathway in bone ( Zarei et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt/β-catenin signaling pathway was significantly activated in male mice, resulting in faster fracture healing ( Haffner-Luntzer et al, 2021 ). Also, sex differences using a murine long bone critical-size defect model were compared; MSC-based therapy enhanced bone bridging with increased ALP expression especially in male mice ( Ueno et al, 2021 ). Zarei et al demonstrated sexual dimorphism with genetic and pharmacological modulation of the alternative NF-κB pathway in bone ( Zarei et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data obtained from fifty-four, 10-week-old, female, Lewis rats is reported in this study. Only female rats were used in this study as the experimental creation of atrophic nonunions is known to be reproducible only in female but not in male mice and rats (30,31). Surgical procedures and all animal care was performed in accordance with the protocols and approvals of the University of Virginia Animal Care and Use Committee.…”
Section: Methodsmentioning
confidence: 99%
“…Using a hydrogel laden with interleukin (IL)-4 overexpressing mesenchymal stem cells for treating a critical-size bone defect injury in a murine model showed that healing was enhanced for both male and female mice. However, notable sex differences were observed for functional end points, such as the number of macrophages (M > F) and osteoclasts (F > M) at the site of healing (66).…”
Section: Cellsmentioning
confidence: 97%